Everyday Urban Sounds: Ben Katchor’s Julius Knipl Radio Cartoons - Benjamin Fraser (Comicalités)
This article studies the “radio cartoons” of Julius Knipl’s: Real Estate Photographer, a series of fourteen short audio fictions, produced by David Isay and broadcast online, based on the work of the same title by Ben Katchor. Already very “sonic” in itself, this American comic strip is saturated with the sounds of modern life, and develops a particular use of speech, particularly in terms of linguistic rhythm, which lends itself well to acoustic adaptation. The paper shows how “radio cartoons” remediate both radio and comics, replacing them in the cultural context in which they were broadcast.